Suicide among justice-involved veterans: a brief overview of extant research, theoretical conceptualization, and recommendations for future research. Issue 1 (2nd January 2021) - Holliday, Ryan; Martin, W. Blake; Monteith, Lindsey L.; Clark, Sean C.; LePage, James P.
ABSTRACT: Both justice-involved individuals and veterans are at elevated risk for suicide. Despite this, research examining the intersection between justice involvement and veteran status has been limited. In addition, factors which drive risk for suicidal self-directed violence (i.e. suicide attempt, suicide) among justice-involved veterans remain understudied. This paper serves as a brief overview of extant literature regarding potential psychosocial factors which may drive suicide risk in this population. Additionally, the Interpersonal-Psychological Theory of Suicide is applied to posit specific factors underlying justice-involved veterans' risk for suicidal self-directed violence. Finally, given the limited suicide-focused research specific to justice-involved veterans, we propose specific directions that are needed for subsequent research. In particular, further examination of a conceptual model of suicide risk in this population, as well as methods for intervening on identified risk factors, remain necessary to effectively prevent suicide in this understudied population of veterans.